BIẾN ĐỘNG VÀ MỐI TƯƠNG QUAN CỦA MẬT ĐỘ VI SINH VẬT TRONG MÔI TRƯỜNG NƯỚC, TRẦM TÍCH VÀ CƠ NGHÊU BẾN TRE Meretrix lyrata (Sowerby, 1851) TẠI BÃI NGHÊU XÃ HIỆP THẠNH, HUYỆN DUYÊN HẢI, TỈNH TRÀ VINH - Võ, Hải Thi; Nguyễn, Trịnh Đức Hiệu; Hoàng, Trung Du; Nguyễn, Minh Hiếu (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
VARIATIONS AND CORELLATIONS OF BACTERIA DENSITY AMONG SEAWATER, SEDIMENT AND MUSCLE FROM WHITE HARD CLAM Meretrix lyrata (Sowerby, 1851) COLLECTED AT HIEP THANH COMMUNE, DUYEN HAI DISTRICT, TRA VINH PROVINCE Based on three different sample collections (beginning, mid-season and the end of harvest season) of seawater, sediment and Ben Tre white hard clams Meretrix lyrata at Hiep Thanh commune, Tra Vinh province. The results of bacterial density from the above environments revealed that Coliform and Vibrio in both seawater and sediment are safe at density, below the permitted level for aquaculture area (Coliform<104MPN/100ml, QCVN08:2008/BTNMT; Vibrio <105cfu /100ml, TCN101:1997). Notably, the density of Vibrio, Coliform in both sediment and seawater, and Vibrio, E. coli in clam muscle at the harvest time are higher than those in the beginning, mid-season. Especially, Vibrio in the tissue showed higher values than the permitted standard (<300cfu/100g, WHO. 1990). The Pearson’s correlations showed that there were statistically positive correlations between Coliform/Vibrio in seawater, sediment and muscle. Therefore, the increasing of bacteria density in both seawater and sediment could cause an increase in bacteria density in the clam muscle.